PDXNet portal: patient-derived Xenograft model, data, workflow and tool discovery. Issue 2 (22nd April 2022) - Koc, Soner; Lloyd, Michael W; Grover, Jeffrey W; Xiao, Nan; Seepo, Sara; Subramanian, Sai Lakshmi; Ray, Manisha; Frech, Christian; DiGiovanna, John; Webster, Phillip; Neuhauser, Steven; Srivastava, Anuj; et al.
Abstract: We created the PDX Network (PDXNet) portal (https://portal.pdxnetwork.org/ ) to centralize access to the National Cancer Institute-funded PDXNet consortium resources, to facilitate collaboration among researchers and to make these data easily available for research. The portal includes sections for resources, analysis results, metrics for PDXNet activities, data processing protocols and training materials for processing PDX data. Currently, the portal contains PDXNet model information and data resources from 334 new models across 33 cancer types. Tissue samples of these models were deposited in the NCI's Patient-Derived Model Repository (PDMR) for public access. These models have 2134 associated sequencing files from 873 samples across 308 patients, which are hosted on the Cancer Genomics Cloud powered by Seven Bridges and the NCI Cancer Data Service for long-term storage and access with dbGaP permissions. The portal includes results from freely available, robust, validated and standardized analysis workflows on PDXNet sequencing files and PDMR data (3857 samples from 629 patients across 85 disease types). The PDXNet portal is continuously updated with new data and is of significant utility to the cancer research community as it provides a centralized location for PDXNet resources, which support multi-agent treatment studies, determination of sensitivity and resistance mechanisms, and preclinical trials. Graphical Abstract: